(untitled) (Damascus University Journal for the economic and Political sciences, 2023)
The research aimed to know the role of the external auditor’s commitment to CPE in the implementation of advanced AP. The study also sought to introduce the concept of CPE and also introduce the concept of advanced AP. The descriptive analytical approach was used to test the hypotheses of the study, and the main study tool (the questionnaire) was distributed. On the sample of the study represented by some of Syrian auditing firms and offices, 30 questionnaires were retrieved with 100 % of them, which were analyzed using measures of central tendency, correlation and regression tests. The study concluded the following results: The auditing companies operating in Syria are not committed to CPE and do not apply advanced AP, as it was found from the views of the study sample that there is a positive role for continuing professional education on the application of advanced analytical procedures in the audit process. The study recommended the adoption of CPE curriculum by audit firms and offices in Syria, with the need to oblige professional and supervisory bodies to adopt topics related to modern techniques in data analysis to improve the reality of the profession’s work and develop performance in a clear and effective manner